Intravenous Topiramate: Pharmacokinetics in Dogs with Naturally Occurring Epilepsy - Vuu, Irene; Coles, Lisa D.; Maglalang, Patricia; Leppik, Ilo E.; Worrell, Greg; Crepeau, Daniel; Mishra, Usha; Cloyd, James C.; Patterson, Edward E. (Frontiers in Veterinary Science, 2016)
Barriers to developing treatments for human status epilepticus (SE) include the inadequacy of experimental animal models. In contrast, naturally-occurring canine epilepsy is similar to the human condition and can serve as a platform to translate research from rodents to humans. The objectives of this study were to characterize the pharmacokinetics (PK) of an intravenous (IV) dose of topiramate (TPM) in dogs with epilepsy, and evaluate its effect on intracranial electroencephalographic (iEEG) features. Five dogs with naturally occurring epilepsy were used for this study. Three were getting at least one antiseizure drug as maintenance therapy including phenobarbital (PB). Four (ID 1-4) were used for the 10 mg/kg IV TPM + PO TPM study, and three (ID 3-5) were used for the 20 mg/kg IV TPM study. IV TPM was infused over 5 minutes at both doses. The animals were observed for vomiting, diarrhea, ataxia, and lethargy. Blood samples were collected at scheduled pre- and post-dose times. Plasma concentrations were measured using a validated HPLC-MS method. Non-compartmental and population compartmental modeling were performed (Phoenix WinNonLin and NLME) using plasma concentrations from all dogs in the study. Intracranial EEG (iEEG) was acquired in one dog. The difference between averaged iEEG energy levels at 15 minutes pre- and post-dose was assessed using a Kruskal-Wallis test. No adverse events were noted. Topiramate concentration-time profiles were best fit by a two-compartment model. PB co-administration was associated with a 5.6 fold greater clearance and a 4 fold shorter elimination half-life. iEEG data showed that TPM produced a significant energy increase at frequencies >4 Hz across all 16 electrodes within 15 minutes of dosing. Simulations suggested that dogs on an enzyme inducer would require 25 mg/kg, while dogs on non-inducing drugs would need 20 mg/kg to attain the target concentration (20-30 µg/mL) at 30-minutes post-dose. This study shows that IV TPM has a relatively rapid onset of action, loading doses appear safe, and the presence of PB necessitates a higher dose to attain targeted concentrations. Consequently, it is a good candidate for further evaluation for treatment of seizure emergencies in dogs and people.